Household Size and Household Wealth in Indonesia with the Influence of Spatial Aspects - Soseco, Thomas (Economics and Finance in Indonesia, 2022)
Investigating household wealth should also include spatial analysis to capture the influence of location on the households’ net wealth and to avoid underestimation of the effect of the change of variables due to estimation that ignores spatial aspects. This paper examines factors influencing household net wealth in Indonesia with the influence of spatial lag using data from the Indonesian Family Life Survey (IFLS) for 1993–2014. The article relies on the Spatial Durbin Model (SDM) to analyze the data. Results show that household net wealth in Indonesia is spatially related to each other, and the spillover effect makes the change of household net wealth in Indonesia dominated by the change of variables in neighbouring regions. Furthermore, considering the time component, there is a positive effect of households’ size on households’ net wealth due to the time component concerning the spatial lag of the dependent and independent variables.